A global analysis of the complex landscape of isoforms and regulatory networks of p63 in human cells and tissues. (December 2015) - Sethi, Isha; Romano, Rose-Anne; Gluck, Christian; Smalley, Kirsten; Vojtesek, Borivoj; Buck, Michael; Sinha, Satrajit
Abstract Background The transcription factor p63 belongs to the p53/p63/p73 family and plays key functional roles during normal epithelial development and differentiation and in pathological states such as squamous cell carcinomas. The humanTP63 gene, located on chromosome 3q28 is driven by two promoters that generate the full-length transactivating (TA) and N-terminal truncated (ΔN) isoforms. Furthermore alternative splicing at the C-terminus gives rise to additional α, β, γ and likely several other minor variants. Teasing out the expression and biological function of each p63 variant has been both the focus of, and a cause for contention in the p63 field. Results Here we have taken advantage of a burgeoning RNA-Seq based genomic data-sets to examine the global expression profiles of p63 isoforms across commonly utilized human cell-lines and major tissues and organs. Consistent with earlier studies, we find ΔNp63 transcripts, primarily that of the ΔNp63α isoforms, to be expressed in most cells of epithelial origin such as those of skin and oral tissues, mammary glands and squamous cell carcinomas. In contrast, TAp63 is not expressed in the majority of normal cell-types and tissues; rather it is selectively expressed at moderate to high levels in a subset of Burkitt's and diffuse large B-cell lymphoma cell lines. We verify this differential expression pattern of p63 isoforms by Western blot analysis, using newly developed ΔN and TA specific antibodies. Furthermore using unsupervised clustering of human cell lines, tissues and organs, we show that ΔNp63 and TAp63 driven transcriptional networks involve very distinct sets of molecular players, which may underlie their different biological functions. Conclusions In this study we report comprehensive and global expression profiles of p63 isoforms and their relationship to p53/p73 and other potential transcriptional co-regulators. We curate publicly available data generated in part by consortiums such as ENCODE, FANTOM and Human Protein Atlas to delineate the vastly different transcriptomic landscapes of ΔNp63 and TAp63. Our studies help not only in dispelling prevailing myths and controversies on p63 expression in commonly used human cell lines but also augur new isoform- and cell type-specific activities of p63.